Differential resistance of insect sodium channels with kdr mutations to deltamethrin, permethrin and DDT. - Burton, M.J.; Mellor, I.R.; Duce, I.R.; Davies, T.G.; Field, L.M.; Williamson, M.S. (Insect Biochemistry and Molecular Biology, 2011)
Knockdown resistance (kdr) in insects, caused by inherited nucleotide polymorphisms in the voltage-gated sodium channel (VGSC) gene, is a major threat to the efficacy of pyrethroid insecticides. Classic kdr, resulting from an L1014F substitution in the VGSC is now present in numerous pest species. Two other substitutions at the L1014 locus have also been reported, L1014S and L1014H. Here we have used expression of L1014 modified Drosophila para VGSCs in Xenopus oocytes with two-electrode voltage clamp to characterise all three mutations. The mutations L1014F and L1014H caused significant depolarizing shifts in the half activation voltage (V(50,act)) from -17.3 mV (wild-type) to -13.1 and -13.5 mV respectively, whereas L1014S caused no shift in V(50,act) but its currents decayed significantly faster than wild-type channels. Treatment of the wild-type channel with deltamethrin (? 1 nM), permethrin (? 30 nM) or DDT (? 1 ?M) resulted in hyperpolarizing shifts in V(50,act). Deltamethrin, permethrin and DDT also produced "tail currents" with EC??s of 0.043, 0.40 and 65 ?M and maximum modifications of 837, 325 and 7% respectively. L1014F provided a high level of resistance against all insecticides for both measured parameters. L1014H most effectively combated deltamethrin induced tail currents while L1014S strongly resisted the large DDT induced shifts in V(50,act). We conclude that L1014H and L1014S may have arisen through heavy exposure to specific pyrethroids and DDT respectively.